MENINGKATKAN PEMAHAMAN SISWA MENGGUNAKAN PENDEKATAN JELAJAH ALAM SEKITAR (JAS) DENGAN METODE EKSPERIMEN PADA MATERI LIMBAH - Erwan, Erwan; Achyani, Achyani (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
Student understanding isÂ how a student is able to maintain, differentiated, assumed, explains, and What has been received. Understanding rather than merely thinking activities, but did experience the mind (experience life). The things to doÂ to achieve student understandingÂ is by ways student actively exploring learn directly.Â Â Approach to natural roamingÂ around alternative in learning biology. In this approach, student are required actively exploring, learning envirotment as a source of biology, will be able to increase studentâs understanding. Conclusions of this study, learning opproach to natural roamingÂ around with experimental methods can increase studentâs understanding in SMA Muhammadiyah 2 Metro school year 2011/2012 of pre-PTK to the cycle 2 be 54% and suggestion that research can be used increase the studentâs understanding.Kata Kunci: Jelajah Alam Sekitar, Aktivitas Belajar, Hasil Belajar